ANALISIS KINERJA SAHAM SYARI’AH SEKTOR ENERGI MENGGUNAKAN PENDEKATAN ANALISIS FUNDAMENTAL DAN TEKNIKAL DI BEI PRIODE 2024 - apriani, Wanti; Evan Setiawan; Nurrahmah Putry (JSE: Jurnal Sharia Economica, 2026)
This study aims to analyze the performance of sharia stocks in the energy sector listed on the Indonesia Stock Exchange (IDX) for the 2024 period using fundamental (ROE, EPS, and PER )  and technical analysis (. SMA and RSI )  approaches indicators to identify trends and signals of stock price movements. This study employed a quantitative approach with descriptive analytical methods. The results indicate that fundamental and technical analysis provide different but complementary perspectives in assessing the performance of sharia stocks. Fundamental analysis emphasizes the company's financial condition, while technical analysis provides information regarding the appropriate timing for investment decisions.Therefore, the combination of these two approaches can help investors make more optimal, accurate, and sharia-compliant investment decisions.